373 Systematic literature review of efficacy and safety of first-line maintenance therapy trials in advanced ovarian cancer. (4th December 2020) - Guy, Holly; Travers, Karin; Hawkes, Carol; Walder, Lydia; Malinowska, Izabela; Gupta, Divya
Abstract : Introduction/Background: Maintenance therapies have changed the treatment landscape in ovarian cancer (OC) in recent years. Here we sought to review safety and efficacy outcomes in clinical trials of first-line maintenance therapies. Methodology: A systematic literature review (SLR) was performed on 27 February 2020 to identify clinical outcomes associated with first-line maintenance therapies and maintenance therapies initiated alongside first-line chemotherapy followed by a maintenance phase for advanced OC. Randomised controlled trials (RCTs), non-RCTs and observational studies were eligible. Selection criteria following the PICOS (population, interventions, comparators, outcomes and study type) principle were specified. Outcomes of interest were progression-free survival (PFS), overall survival (OS), and treatment emergent adverse events (TEAEs). Selected studies were then extracted by one reviewer and assessed for quality by a second reviewer. Disagreements were resolved by a third reviewer when required. Results: This SLR retrieved 8, 631 unique references of which a total of 50 references were accepted and extracted in this SLR (figure 1 ). The 50 references identified covered 18 clinical trials that evaluated maintenance therapies in OC patients following one prior line of chemotherapy. Of these 18 trials, 12 were RCTs and the remaining 6 were observational, dose escalation and retrospective review studies. Of the 18 trials, only 2 did not assess PFS as an efficacy endpoint (NCT00058435 and MIMOSA). PARP inhibitors across the board reported a better PFS hazard ratio (HR) than other OC maintenance therapies (table 1 ). No pattern was identified in relation to PFS amongst patients who were treated with a maintenance therapy following first-line platinum-based chemotherapy versus those who received a maintenance drug concurrently with first-line platinum-based chemotherapy and then continued with the maintenance treatment. OS was reported as a secondary endpoint in 12 trials (MIMOSA, AGO-OVAR16, SOLO-1, ICON-7, GOG-0218, AGO-OVAR12, VELIA/GOG-3005, TRINOVA-3, ESME, CHIVA/GINESCO, PRIMA and PAOLA-1). Only PARP inhibitor-containing therapies reported significant OS HRs below 1 across all trial populations. TEAEs were reported for 11 of the 18 trials. Discontinuation due to AEs was reported in 10 of the 18 trials. Conclusion: Therapies that included PARP inhibitors reported better PFS HR than other OC maintenance therapies. In study populations including both BRCA mutation positive and wild type, clinical benefit is conferred by both olaparib plus bevacizumab and niraparib as indicated by PFS. OS data remain immature. Disclosures: This study was funded by GlaxoSmithKline. Clinical Trial Registration: N/A Dr Guy and Walder report institutional reimbursements from GlaxoSmithKline. Drs. Travers, Hawkes, Malinowska, and Gupta are employees of GlaxoSmithKline.